1992
DOI: 10.1002/ajim.4700220502
|View full text |Cite
|
Sign up to set email alerts
|

Introduction: Health and safety education for worker empowerment

Abstract: This article introduces a special issue of the American Journal of Industrial Medicine dedicated to innovative approaches to worker education in health and safety. Contributors to this issue describe applications of an "empowerment approach" in a wide variety of institutions and settings throughout the United States and Canada. In this article, empowerment education is presented and contrasted with other training methodologies. The article offers suggestions on how to implement this approach discusses evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 33 publications
0
47
1
6
Order By: Relevance
“…Un autre exemple, dans le domaine psychosocial, est l'organisation de programmes psycho-éducatifs de gestion du stress. D'autres exemples innovants de formations des travailleurs dans le domaine des risques professionnels et faisant appel notamment à la notion d'empowerment sont décrits dans un numéro spécial de l'American Journal of Industrial Medicine [36]. D'autres stratégies consistent en des actions structurées basées sur des modèles de changement comportemental [8,9] La participation et l'action communautaire Une deuxième stratégie utilisée est la participation, présente d'abord à travers un système de représentation paritaire, pilier des modèles de concertation sociale depuis la fin de la deuxième guerre mondiale.…”
Section: Les Actions éDucatives En Vue Du Développement Des Aptitudesunclassified
“…Un autre exemple, dans le domaine psychosocial, est l'organisation de programmes psycho-éducatifs de gestion du stress. D'autres exemples innovants de formations des travailleurs dans le domaine des risques professionnels et faisant appel notamment à la notion d'empowerment sont décrits dans un numéro spécial de l'American Journal of Industrial Medicine [36]. D'autres stratégies consistent en des actions structurées basées sur des modèles de changement comportemental [8,9] La participation et l'action communautaire Une deuxième stratégie utilisée est la participation, présente d'abord à travers un système de représentation paritaire, pilier des modèles de concertation sociale depuis la fin de la deuxième guerre mondiale.…”
Section: Les Actions éDucatives En Vue Du Développement Des Aptitudesunclassified
“…Ela incorpora o diálogo entre educadores e trabalhadores, e analisa criticamente a organização e as causas sistêmicas dos problemas no ambiente de trabalho. 37 De acordo com este conceito, a solução para os problemas de saúde ocupacional nos abatedouros deveria partir dos próprios trabalhadores, por meio de participação democrática e ativa.…”
Section: Veterinários Como Educadores Para O Empowermentunclassified
“…Da mesma maneira, não se conhece os fatores que infl uenciam esses esforços, conforme ressaltados de estudos sobre outros tipos de trabalho de alto risco. 13,19 A educação de trabalhadores em indústrias, de modo geral, tem sido baseada apenas na aquisição de competências, 37 porém, em um cenário ideal, a mudança de comportamento não deveria ser o único objetivo. A formação profi ssional dos veterinários, por outro lado, historicamente não contempla temas relacionados à prática educacional, constituindo obstáculo para projetos de educação para trabalhadores que prestam serviços na área veterinária.…”
Section: Veterinários Como Educadores Para O Empowermentunclassified
“…These laws are enforced by different ministries and departments of the Government. According to Wallerstein and Weinger, (1992); three major problems need to be addressed before the field of worker health and safety education can advance: the lack of clarity and consensus on the goals of worker education; lack of standards for effective teaching methods, including the lack of skills in these methods of the people who deliver the trainings and inadequacy of program evaluation. The ILO, 2013 cited the Kenya Economic Survey of 2010 and indicated that the total number of employed persons in Kenya in all sectors in the year 2010 was 10,960,000.…”
Section: Work Environmentmentioning
confidence: 99%